Psychological Attributes, Stressors, and Coping of Older Adults Teaching in Selected State Universities in Manila, Philippines - De Jose, Elmer (Social Sciences and Development Review, 2016)
This paper examined the psychological attributes of older adults ranging from 55 years old and above who teach in selected state universities in Manila, Philippines. Psychological attributes, in this study, include self concept, and their perception about the changes in their bodily, cognitive, and social attributes. Two hundred six (206) pre-retirees (55 to 64 years old) and retirees (65 years old and above) participated in the study. Results revealed that the older adults described themselves as generally friendly and generous, feel secured and competent, assertive, emotionally strong, and are contented and happy about life. They graciously acknowledged the changes in the physical, physiological, cognitive, and social attributes concomitant with aging. The stressors experienced by some of them within the last two years include: bereavement stressors—death of spouse, death of a family member and a close friend; family-related stressors —separation with child, and serious illness/injury of a family member; and work-related stressors—conflict with superiors and/or subordinates, and major career changes. Few have disclosed having experienced incidence of physical and verbal assaults, and financial exploitation. Various spiritual, cognitive, and social support mechanisms were resorted to by the respondents to cope with the experienced changes and stressful events. Implications for practice and research were discussed.
Keywords: older adults; retirees; pre-retirees; psychological attributes; self-concept; stressors; coping mechanisms